Some personal reminiscences on Yuri Kondratiev and the impact of his research - Albeverio, Sergio; Bock, Wolfgang; Streit, Ludwig (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9 We sketch a strong impact of the works by Yuri Kondratiev in various fields of science. In particular, after a more personal literature review of his studies, we briefly give two examples in which the theoretical results of Yuri Kondratiev changed the situation in the corresponding research theories.